A compact design of multi-feeder data logging system for power quality measurement with a multiplexer and a single PQ transducer - Hendri Novia Syamsir; Dalila Mat Said; Yusmar Palapa Wijaya (National Research and Innovation Agency, 2017)
This paper presents a simple and costs effective equipment design multi-feeder data logger for recording and monitoring power quality. The system design uses remote supervising and multi-feeder data logging system (RESMOS). The data collected through resmos portable unit (RMPU) will automatically be saved with the format as binary and comma separated value (CSV). The time setting on the RMPU can be configured with minimum one minute per logging. This data logger uses a single transducer with a multiplexer for recording and monitoring ten channels of power quality at busbar. The system design has been validated with national metrology laboratory scientific and industrial research institute of Malaysia (SIRIM). This tool has the advantage that it can be used to measure harmonic data more than 21st at the same time for ten channels and equipped with software making it easier for analysis data with low operational costs versus another power quality equipment. The experimental results indicate that the proposed technique can accelerate data reading with conversion rate one sample per second for each channel. The device can be used to measure harmonic level and power quality with a confidence level above 95% and percentage error under 2.43% for total harmonics distortion (THD) and 1.72% for voltage harmonics.